Global Corporate Executives’ SOCIAL CAPITAL Formation Experiences - Yoshie Tomozumi Nakamura (Adult Education Research Conference, 2009)
There is growing interest in examining social capital and how it influences communities, organizations, and individuals. This research seeks to determine how social capital is developed among senior executives in a global organization.